A nomogram for predicting the risk of male breast cancer for overall survival - Wen, Yahui; Bai, Junjie; Zheng, Caihong; Liu, Jiameng; Lin, Shunguo; Han, Hui; Xu, Chunsen (Frontiers in Oncology, 2023)
Male breast cancer (MBC) is a rare disease, accounting for <1% of all male carcinomas. Due to the lack of prospective data, the current therapy for MBC is based on retrospective analysis or information that is extrapolated from studies of female patients. In this study, we aimed to construct a nomogram model to predict the overall survival (OS) of Male breast cancer (MBC) patients and verify its feasibility using data from China. A total of 1224 MBC patients from the Surveillance, Epidemiology and End Results (SEER) registry between 2010 and 2015 were in the training cohort and 44 MBC patients from the Fujian Medical University Union Hospital in the validation cohort. T status(p<0.001), age at diagnosis(p<0.001), histologic grade(p=0.008), M status(p<0.001), ER status (p=0.001), Her2 status(p=0.019), chemotherapy(p=0.015) and surgery type (p=0.001) were independently associated with OS. The diagnostic performance of this model was evaluated and validated using ROC curves on the training and validation datasets. In the training cohort, the nomogram-predicted AUC value was 0.786 for 3-year OS and 0.767 for 5-year OS. In the validation cohort, the nomogram-predicted AUC value was 0.893 for 3-year OS and 0.895 for 5-year OS. The nomogram developed in this study, which incorporated these variables, showed good discrimination and good calibration. Decision curve analysis demonstrated that the nomogram was more beneficial than the AJCC stage.